APPLICATION OF INDICATORS IN PALOTINA CITY - PR - dos Santos, R. F.; Cabral, A. C.; Frigo, E. P.; Bastos, R. K.; Placido, H. F.; Pinto, L. P. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The environmental health indicator (ISA), was developed to evaluate and characterize the effectiveness of public policies, aiming at improving the quality of life of the population through the qualification and quantification of environmental health of a region or municipality. The methodology of ISA has been proposed in the state of São Paulo in 1999, and the same applied in Palotina, whose calculation is performed by the weighted average of sub-indicators, indicate an average of 78.48 health outcome for the city.